Sacrilege, Tractarian Fiction and the Very Long Reformation. Issue 2 (3rd July 2019) - Shell, Alison
ABSTRACT: The Tractarian movement in the nineteenth-century Church of England brought new life to Reformation-era issues. One such was the notion of sacrilege, especially associated with Catholics and high-churchmen. Responding to reformist destruction of religious houses and the lay impropriation of monastic lands and revenues, believers in sacrilege asserted that those who damaged sacred objects or stole from the church risked divine displeasure. The seventeenth-century commentator Henry Spelman's writings on sacrilege were reprinted in the nineteenth century, and his warning that the descendants of impropriators would suffer for the sins of their ancestors was widely embraced. This essay examines how two Tractarian writers, John Mason Neale (1816–66) and Charlotte M. Yonge (1823–1901), engaged with ideas of sacrilege in their fiction.